Pengaruh Lingkungan Kerja, Disiplin Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan - Choeroh, Nikmatul; Nawatmi, Sri (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
This research is to determine the influence of the work environment, work discipline and job satisfaction on employee performance (Study at the Population and Civil Registration Service). The type of data used is primary. With a population of 124 employees, 95 respondents were obtained after applying the purposive sampling method with the Solvin formula, with an assessment using a Likert scale. The data analysis technique uses Multiple Linear Regression. From the results of hypothesis testing on employee performance, it is known that the work environment and work discipline have a positive effect on employee performance, while job satisfaction has no effect on employee performance. The coefficient of determination (R Square) is 0.758, which means that 75.8% of the variation of all independent variables (work environment, work discipline, and job satisfaction) can explain the dependent variable (employee performance), while the remaining 24.2% is explained by the variable free and not included in this study.